French Cultural Standards from Czech Perspective in Study Environment - Sádlová, Barbora; Křečková Kroupová, Zuzana, 1972-; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The Czech Republic and the French Republic are both situated in the European continent and only one other country lays between them. Geographically are very close, however, culturally are very different. At the first glance, the distinctions might not be so significant. However, commonly after the arrival, a foreign student experiences misunderstandings, inconvenient situations and cultural shock due to the lack of knowledge of the unfamiliar culture. Therefore, it is essential to understand the differences in order to successfully integrate and ease the stay while studying abroad. This Bachelor thesis concentrates on cultural standards of Alexander Thomas and how they influence everyday life of the Czech students in France. The main aim is to define the Czech-French cultural standards and compare them with the theory. Also, the standards will be applied on the historic-cultural aspects. At the end of this Bachelor thesis, the recommendations and guidance will be provided for those students interested in studying in the French Republic.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses